Global optimization-based calibration algorithm for a 2D distributed hydrologic-hydrodynamic and water quality model - Gomes, Marcus Nóbrega; Giacomoni, Marcio Hofheinz; Navarro, Fabricio Alonso Richmond; Mendiondo, Eduardo Mario (Environmental modelling & software : with environment data news, 2024)
Hydrodynamic models with rain-on-the-grid capabilities are usually computationally expensive for automatic parameter estimation. In this paper, we present a global optimization-based algorithm to calibrate a fully distributed hydrologic-hydrodynamic and water quality model (HydroPol2D) using observed data (i.e., discharge, or pollutant concentration) as input. The algorithm finds near-optimal set of parameters to explain observed gauged data. This framework, although applied in a poorly-gauged urban catchment, is adapted for catchments with more detailed observations. The results of the automatic calibration indicate NSE = 0.99 for the V-Tilted catchment, RMSE = 830 mg L-1 for salt concentration pollutograph in a wooden-plane (i.e., 8.3% of the event mean concentration), and NSE = 0.89 in a urban real-world catchment. This paper also explores the issue of equifinality (i.e., multiple parameters giving the same calibration performance) in model calibration indicating the performance variation of calibrating only with an outlet gauge or with multiple gauges within the catchment. [Display omitted] •An automatic calibration algorithm for distributed flood and water quality modeling is developed.•It uses HydroPol2D model and calibrate water quantity and quality parameters globally.•Data from observed gauges such as discharges, depths, and concentration is used for calibration.•Poorly placed gauges and low runoff events can increase equifinality during calibration.